Optimalisasi Kinerja Sistem Transaksi Melalui Pengembangan Aplikasi Kasir Berbasis Mobile Android - Mualif, Farhan; Ikrimach, Ikrimach (Institut Informatika Dan Bisnis Darmajaya, 2024)
This research aims to develop an Android mobile-based cashier application system at Toko Nay Sahabat Alam. The store currently does not have a system that facilitates the sales transaction process, inventory management, and sales and purchase history in a structured manner, which results in less efficient business processes and the risk of operational errors. The proposed cashier application is designed to optimize the sales transaction process, stock inventory management, and display sales and purchase history. The system architecture is implemented using Rest API, with the backend developed using Laravel framework and MySQL database management system. Android mobile application development using Flutter. The development methodology used is agile. Testing is done using the black-box testing method and the results show that all application features run as expected. End-user testing was also conducted using a questionnaire to measure user satisfaction with the application. The questionnaire results showed that most users were satisfied with this application as a whole, with 57.1% of respondents giving the highest score of 5, 35.7% giving a score of 4, and 7.1% giving a neutral score of 3. The system implementation results can improve operational efficiency, minimize errors in the transaction process, and facilitate more effective transaction and inventory data management.